Высокоинтерактивный электронный учебник по курсу «Компьютерная графика» - Дударь, З. В.; Черепахин, В. М.; Черепахина, Е. В. (УАДО, 2004)
The proposed textbook may be applied for various disciplines that are connected with computer graphics. Embedded in different types of lessons algorithm models have a number of parameters which can be adjusted. This enables to better understand the algorithm functioning in different situations.
Keywords: электронный учебник; компьютерная графика